Trends and outcomes of fertility preservation for girls, adolescents and young adults with Turner syndrome: A prospective cohort study - Rodriguez-Wallberg, Kenny A.; Sergouniotis, Fotios; Nilsson, Hanna P.; Lundberg, Frida E. (Frontiers in Endocrinology, 2023)
Background: In Scandinavian countries, programs for fertility preservation (FP) are offered free of charge at tertiary-care university hospitals to all patients facing infertility risks due to malignant diagnoses or benign conditions. In this prospective study we aimed to investigate trends and outcomes of FP indicated by a diagnosis of Turner syndrome. Methods: Prospective cohort study of patients with Turner karyotype receiving fertility preservation counselling at the Karolinska University Hospital between 1 January 1999 and 31 December 2021. Results: The cohort included 100 women and girls that received counselling, whereof 27% were prepubertal girls, 59% were adolescents and 14% of adult age. Before 2006 all patients were referred for fertility counselling at the time of Turner diagnosis. Based on updated guidelines, mainly patients who showed signs of puberty were referred after 2006. As a result, spontaneous menarche was more common in the later period. In total, 39% of the cohort had monosomal karyotype (45X), 20% had 45X/46XX or 45X/47XXX mosaicisms and 36% had an X-chromosomal structural anomaly. Ovarian tissue cryopreservation was planned for 73% of all patients, and oocyte cryopreservation following gonadotropin stimulation was planned for 10% of the patients. Follicles were present in 25% of all biopsies analyzed. Adolescents were more likely to have follicles present (30%) than prepubertal girls (16%) or adult women (17%). The ten patients that underwent gonadotropin stimulation for oocyte cryopreservation underwent a total of 15 cycles and eight patients successfully preserved oocytes. In total, 26% of the cohort has undergone fertility treatment or expressed further interest in fertility preservation. Six women have given birth using donated oocytes and three following spontaneous conception. Two women have undergone re-transplantation of cryopreserved ovarian tissue, without regaining ovarian function, and none of the women that have cryopreserved oocytes has returned to use them. Conclusion: Fertility counselling for girls with Turner syndrome should ideally be offered at onset of spontaneous puberty to improve the chances of fertility preservation. Since the girls and women in this cohort are still young, the return rate and utilization of the preserved tissue and oocytes is expected to increase with time. Study Registration: ClinicalTrials.gov NTC04602962